Reforming public expenditure in industrialised countries: are there trade-offs? - Ludger Schuknecht; Vito Tanzi (European Central Bank (ECB), 2005)
In this paper, we show that, contrary to common beliefs, over the past two decades several countries were able to reduce public spending by remarkable amounts. These countries did not seem to have suffered from these large reductions either in a macroeconomic sense, or in terms of lower values for socio-economic indicators. On the contrary, ambitious expenditure reform coincides with improvements in fiscal, economic, human development and institutional indicators. Positive developments associated with expenditure reform, in some instances, have taken a while to materialize and early and persistent reformers have, hence, already seen more of them. Unfavourable effects on income distribution within countries are small and they are mitigated in absolute terms by faster growth in the medium run and by the possibilities of better targeting of public spending. Moreover, there is significant divergence across countries that suggests that country circumstances and reform design matter.
Keywords: H5; H6; O57; 330; Economic Growth; expenditure reform; public expenditure; socio economic indicators; Öffentliche Ausgaben; Finanzreform; OECD-Staaten; Wirkungsanalyse